EFEKTIVITAS PENGGUNAAN AUGMENTED REALITY (AR) DALAM MENINGKATKAN HASIL BELAJAR SISWA SD PADA MATA PELAJARAN IPA: LITERATURE REVIEW - Widya Mufidatul ‘Ula; Eka Duwi Ardianti; Nadya Ayu Lifiani; Mu’minatut Towafiah; Audy Putri Cahyani; Nurul Mahruzah Yulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning is an activity carried out by each individual with the aim of causing a change in behavior from interaction with the environment and learning resources. Digital technology has opened up new opportunities for educational transformation as an innovation and improvement in the quality of learning, especially in improving the effectiveness of learning at the Elementary School level, one of which is Augmented Reality (AR) with a learning concept that combines the real world with virtual elements in real-time. This study adopts a literature review method by collecting and analyzing "various sources such as books, research reports, journals, and articles related to the effectiveness of using AR in improving elementary school student learning outcomes in Natural Sciences (IPA) subjects". The discussion concludes that the application of Augmented Reality (AR) technology in the Natural Sciences (IPA) learning process at the Elementary School (SD) level has a positive effect on student learning outcomes. An increase in the average posttest score compared to the pretest was found in almost all studies reviewed, with a significant increase, 3D visualization and AR interactivity have been proven to help students understand materials such as the respiratory system, solar system, plant parts, and others. AR creates more fun and challenging learning, encouraging students to more actively explore the material.